2019
DOI: 10.1007/s00586-019-06157-0
|View full text |Cite
|
Sign up to set email alerts
|

The association of cervical sagittal alignment with adjacent segment degeneration

Abstract: Purpose Cervical spine surgery may affect sagittal alignment parameters and induce accelerated degeneration of the cervical spine. Cervical sagittal alignment parameters of surgical patients will be correlated with radiological adjacent segment degeneration (ASD) and with clinical outcome parameters. Methods Patients were analysed from two randomized, double-blinded trials comparing anterior cervical discectomy with arthroplasty (ACDA), with intervertebral cage (ACDF) and without intervertebral cage (ACD). C2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…In the current study, we did not find that these cervical sagittal parameters had any impact on the patientreported outcomes after CDR, which was consistent with the results reported by Yang et al [24] However, Guerin et al [25] reviewed the data of 40 Mobi-C CDR patients and found significant positive correlations between postoperative SA and the postoperative SF-36 score (r = 0.349, P = 0.027) and between the postoperative shell angle and postoperative VAS neck pain score (r = 0.422, P = 0.007). Shen et al [23] measured the T1s in 90 patients who underwent one-level Bryan CDR and found that a higher T1s was related to more obvious neck pain at the 6-year follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we did not find that these cervical sagittal parameters had any impact on the patientreported outcomes after CDR, which was consistent with the results reported by Yang et al [24] However, Guerin et al [25] reviewed the data of 40 Mobi-C CDR patients and found significant positive correlations between postoperative SA and the postoperative SF-36 score (r = 0.349, P = 0.027) and between the postoperative shell angle and postoperative VAS neck pain score (r = 0.422, P = 0.007). Shen et al [23] measured the T1s in 90 patients who underwent one-level Bryan CDR and found that a higher T1s was related to more obvious neck pain at the 6-year follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have shown that there is a relationship between cervical sagittal balance and neck pain, cervical disc degeneration, and the outcomes of ACDF. 3,4,7,[9][10][11][12]21,26 However, the importance of cervical sagittal parameters in CDR is rarely noted. In addition, the cervical sagittal alignment and its impacts on clinical outcomes after Prestige-LP CDR has been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…We measured cervical sagittal alignment parameters on the lateral radiographs according to the methods presented in previous studies (Figure 1). 21,22 The following parameters were evaluated: (1) CL, measured as the angle between the inferior end plate of C2 and the inferior end plate of C7; (2) FSUA, measured as the angle between the superior end plate of the superior vertebra and the inferior end plate of the inferior vertebra at the surgical segment; (3) sagittal cervical axis (SVA), measured as the distance between the plumb line from the center of C2 and the superior posterior corner of C7; and (4) T1s, measured as the angle between the superior end plate of T1 and a horizontal line. When obtaining radiographs, the anterior–posterior view of the cervical spine was taken at first, and patients were required to (1) stand and look straight ahead, with their hips and knees extended; (2) lean their back against the fluorescent screen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACDF has been shown to provide good alignment and TDR to improve cervical ROM [ 18 ]. However, few studies have shown that arthroplasty is superior in maintaining cervical alignment [ 19 ]. For example, TDR did not significantly improve sagittal profiles when compared with other cervical fusion techniques and is therefore not considered a lordosis-producing operation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%